2002
DOI: 10.1128/mcb.22.12.4419-4432.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chk2 Activation and Phosphorylation-Dependent Oligomerization

Abstract: The tumor suppressor gene CHK2 encodes a versatile effector serine/threonine kinase involved in responses to DNA damage. Chk2 has an amino-terminal SQ/TQ cluster domain (SCD), followed by a forkhead-associated (FHA) domain and a carboxyl-terminal kinase catalytic domain. Mutations in the SCD or FHA domain impair Chk2 checkpoint function. We show here that autophosphorylation of Chk2 produced in a cell-free system requires trans phosphorylation by a wortmannin-sensitive kinase, probably ATM or ATR. Both SQ/TQ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
211
3
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(227 citation statements)
references
References 63 publications
(104 reference statements)
12
211
3
1
Order By: Relevance
“…It was shown that ectopic overexpression of Chk2 in 293T cells results in its electrophoretic mobility shift (Figure 2a), 13,32 indicating auto-or transphosphorylation. In fact, electrophoretic mobility shift induced by overexpression of Chk2 was abrogated following treatment of cell extracts with CIP or BAP (data not shown).…”
Section: Effect Of Wip1 On Thr68 Phosphorylation Of Chk2 Induced By Dmentioning
confidence: 98%
See 2 more Smart Citations
“…It was shown that ectopic overexpression of Chk2 in 293T cells results in its electrophoretic mobility shift (Figure 2a), 13,32 indicating auto-or transphosphorylation. In fact, electrophoretic mobility shift induced by overexpression of Chk2 was abrogated following treatment of cell extracts with CIP or BAP (data not shown).…”
Section: Effect Of Wip1 On Thr68 Phosphorylation Of Chk2 Induced By Dmentioning
confidence: 98%
“…It had been shown previously that phosphorylation of Chk2 on Thr68 is required for full activation of Chk2 via auto-(trans-or cis)phosphorylation. [9][10][11][12][13][31][32][33][34] We therefore investigated the role of Thr68-phosphorylation in the electrophoretic mobility shift of Chk2. We found that a Chk2 mutant, the alanine68 mutant (HA-Chk2 (T68A)), did not undergo the mobility shift when overexpressed (data not shown), indicating that Thr68 is required.…”
Section: Effect Of Wip1 On Thr68 Phosphorylation Of Chk2 Induced By Dmentioning
confidence: 99%
See 1 more Smart Citation
“…This ATM-dependent phosphorylation event might be facilitated by the Plk3-mediated phosphorylation of Chk2-Ser73 (Bahassi el et al, 2006). Intermolecular interactions between one phospho-Thr68 Chk2 with the forkhead-associated (FHA) domain of another Chk2 molecule lead to homodimerization of the kinase and autophosphorylation at Thr383 and Thr387 within the activation loop of the catalytic domain that is required for full Chk2 activation (Xu et al, 2002;Schwarz et al, 2003). Interestingly, Thr68 phosphorylation is not required to maintain Chk2 kinase activity after autophosphorylation of its T-loop .…”
Section: Introductionmentioning
confidence: 99%
“…CHK2 SCD and FHA domains, in addition to the kinase activity, are essential in the induction of TTK/hMps1 To identify the regions in CHK2 that are required to induce TTK/hMps1, several CHK2 mutants were made (Figure 3a), all with reported compromised CHK2 activity in vitro (Xu et al, 2002;Figure 3a). These mutants and WT CHK2 were cotransfected with HA-TTK/hMps1 into 293T cells, and the lysates were analysed by western blotting.…”
Section: Resultsmentioning
confidence: 99%